PENERAPAN ASAS PACTA SUNT SERVANDA DALAM PERJANJIAN KREDIT TANPA JAMINAN PADA BANK MANDIRI CABANG PEMBANTU CITRA GARDEN MEDAN - DESSY MONICA EVALINA (PREMISE LAW JURNAL, 2016)
The principle ofpacta sunt servanda is a principle which is found in law of obligations which means that when a contract is signed by both parties, they have to comply with the content of the contract. The research used judicial normative and descriptive analytic. The legal consequences of the principle of pacta sunt servanda in breaching the contract by Bank Mandiri, Citra Garden Sub-Branch, Medan, is that it will get the sanction of legal remedy from the other party that it has to fulfill its performance. The correlation between the principle of facia sunt servanda and the principle of good faith in KTA contract in Bank Mandiri, Citra Garden Sub-Branch, Medan, is that the principle of facia sunt servanda becomes the supporting principle for the implementation of the principle of good faith in which the former will provide legal certainty that the contract has been signed with good faith. Therefore, the correlation between both principles is very close and cannot be separated. Keywords : Principle of Pacta Sunt Servanda, KTA Contract, Bank Mandiri, Citra Garden Sub-Branch